2020
DOI: 10.1128/jvi.02051-19
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Human Cytomegalovirus Glycoprotein O (gO) Exert Epistatic Influences on Cell-Free and Cell-to-Cell Spread and Antibody Neutralization on gH Epitopes

Abstract: Human cytomegalovirus (HCMV) glycoproteins H and L (gH/gL) can be bound by either gO or the UL128 to UL131 proteins (referred to here as UL128-131) to form complexes that facilitate entry and spread, and the complexes formed are important targets of neutralizing antibodies. Strains of HCMV vary considerably in the levels of gH/gL/gO and gH/gL/UL128-131, and this can impact infectivity and cell tropism. In this study, we investigated how natural interstrain variation in the amino acid sequence of gO influences … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 66 publications
(173 reference statements)
2
34
1
Order By: Relevance
“…This last results is in contrast with a previous report from the literature where the TB40-UL148-null virus increases replication in epithelial cells (19). As it was pointed out in a very recent and elegant report, we suppose that this difference may be due to the genetic background of different strains (33). As first, we speculated that the gH/UL116 dimer could recognize a receptor on target cells surface and we purified the complex and checked binding by FACS.…”
Section: Discussioncontrasting
confidence: 68%
“…This last results is in contrast with a previous report from the literature where the TB40-UL148-null virus increases replication in epithelial cells (19). As it was pointed out in a very recent and elegant report, we suppose that this difference may be due to the genetic background of different strains (33). As first, we speculated that the gH/UL116 dimer could recognize a receptor on target cells surface and we purified the complex and checked binding by FACS.…”
Section: Discussioncontrasting
confidence: 68%
“…However, it has more recently been reported that viruses lacking gH/gL/UL128-131 can spread cell to cell, but this is dependent on the gH/gL/gO receptor PDGFRa (48). Furthermore, a recent study by our group demonstrated that switching the UL74 allele in both TR and ME backgrounds could influence the efficiency of cell-to-cell spread, demonstrating that there were epistatic phenomena involved inasmuch as the influence of some UL74 alleles was observed in only one of the two genetic backgrounds (65).…”
Section: Discussionmentioning
confidence: 86%
“…In the case of GPCMV, TAMYC and 22122, strains exhibited 25% difference in the gO amino acid sequence and importantly two N-terminal region glycosylation sites were missing, which potentially alters ability of the viral trimer (gH/gL/gO) to interact with cell receptor PDGFRA which can be influenced by glycosylation [ 30 ]. In HCMV, gO polymorphisms modify virus cell-free and cell-to-cell spread [ 48 ] and this might account for the basis of the TAMYC strain being highly cell-associated but this requires further study. Potentially, there are additional differences between the two GPCMV strains but this also awaits further evaluation.…”
Section: Discussionmentioning
confidence: 99%